Pengaruh Teknik Distraksi Menggunakan Video Animasi Kartun Terhadap Tingkat Kecemasan Pada Pasien Anak Pre Sirkumsisi - Gunawan, Hafid; Indriyati, Indriyati; Aryani, Atik (NHM PRESS, 2025)
Anxiety is something that children often experience before performing circumcision. One of the efforts to help reduce anxiety levels in pre-circumcision children is the provision of distraction techniques using cartoon animation videos. Cartoon movies will provide distraction stimuli in the form of visual, auditory and tactile.Objective to determine the effect of distraction techniques using cartoon animation videos on anxiety levels in pre-circumcision pediatric patients.This type of research is a quasi-experimental study with a one group pre-test post-test design. The sample was 28 children who performed circumcision at Modern Circumcision Sukoharjo with a sampling technique using purposive sampling. The research instrument used cartoon animation video distraction and Visual Analog Scale for Anxiety. Data analysis using Wilcoxon test. Results a total of 26 respondents (92.9%) experienced moderate anxiety, 2 respondents (7.1%) experienced severe anxiety before receiving cartoon animation video distraction. A total of 19 respondents (67.9%) experienced mild anxiety and 9 respondents (2.1%) experienced moderate anxiety after receiving cartoon animation video distraction. The Wilcoxon results showed a significance value of p-value = 0.001. Conclusion there is an effect of distraction techniques using cartoon animation videos on anxiety levels in pre-circumcision pediatric patients at Modern Circumcision Sukoharjo.